2019
DOI: 10.1186/s13045-019-0776-8
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs in cancer metabolism: a review

Abstract: Altered energy metabolism is a hallmark of tumors aiming at supplying necessary nutrients for tumorigenesis and development. These redirected metabolic pathways associated with carbohydrate, lipid and amino acid are orchestrated not only by carcinogenic proteins but by non-coding RNAs. Among them, circular RNA (circRNA), as a kind of novel identified non-coding RNAs, has become the focus of attention. Through binding with corresponding microRNAs or directly contacting proteins, circRNA plays a primarily import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
238
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(239 citation statements)
references
References 85 publications
(93 reference statements)
0
238
0
1
Order By: Relevance
“…CircRNAs are a group of non-coding RNAs with a stable closed-loop structure which prevents them from decomposing by the enzymes [20]. Increasing evidence indicated that circRNAs are closely associated with the progression of NSCLC [21]. For example, inhibition of circRNA VANGL1 suppresses the progression of bladder cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are a group of non-coding RNAs with a stable closed-loop structure which prevents them from decomposing by the enzymes [20]. Increasing evidence indicated that circRNAs are closely associated with the progression of NSCLC [21]. For example, inhibition of circRNA VANGL1 suppresses the progression of bladder cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…11) Recently, circRNAs have been reported to participate in multiple diseases, especially in cancers. 12,13) However, there are currently few reports about circRNAs in DKD. Investigating the role of circRNAs will be vital for understanding the pathogenesis of DKD and providing new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are a class of circular noncoding RNAs that have been observed in a variety of cancers [18][19][20], but their function is still unclear. Due to their special circular structure, circRNAs have high stability and great potential as new tumour markers [21].…”
Section: Discussionmentioning
confidence: 99%